The effects of using digital photographs with Geometer's Sketchpad at 4th Grade - SATICI, AHMET FEYZİ (ELSEVIER SCIENCE BV, 2012)
Research findings have showed that students have difficulties in learning geometry. Physical and virtual manipulatives might help primary students to learn and understand geometry easily. In this research, we have investigated the effects of using digital photographs with Geometer's Sketchpad (GSP) on students' academic achievement at 4th grade. In this regards, instructional materials, achievement tests and worksheets were prepared in accordance with 4th grade curriculum and applied on the students. This quasi-xperimental study was conducted in an elementary school with 50 students at 4th grade. The findings of this study demonstrated that using GSP as a virtual manipulative facilitates students learning. Also, according to the interviews with students, the students have both positive and negative thoughts towards instructional software and GSP as a virtual manipulative. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: Goemeter's Sketchpad; digital photographs; geometry instruction; achievement